Embarazo de alto riesgo obstétrico y patología mental futura en los hijos. Intentando llegar antes - Cano, Bernardo (2020)
Objective: The relationship between high-risk obstetric pregnancy and future mental pathology in children is demonstrated. Method: Qualitative cross-sectional descriptive study that relates the risk factors found in pregnant women with those of mothers of psychiatric patients seen in the Child and Adolescent Psychiatry Service of the same hospital. These two groups and those found in mothers of pediatric patients and a control group of pregnant women with high risk pregnancy are compared. Conclusion: There is a concordance between pregnant women of high obstetric risk and mothers of patients with psychiatric pathology. Recommendations, The agreement between high risk pregnancy and future psychiatric pathology merits designing monitoring systems, psychotherapeutic intervention and psycho-education in pregnant mothers with these characteristics